Imperialist times and its implications for public health - John H. Estrada M (Universidad de Antioquia, 2008)
This articles studies the period called by historians as the Big or Long x i x century. Besides the x i x century by itself, it encompasses the decades that preceded it and the decades of the First World War. All of them belong to the consolidation of imperialism. From the perspective of public health, the Big x i x Century is important because of the transition from hygiene to public health, and the beginning of the bacteriologic theory in 1880, influencing sanitary control measures of the State. Before 1900, medicine was characterized by: 1) predominance of military and of imperial approaches, 2) prevention principles were imported and concentrated in sanitary practices; 3) colonial medicine was not separated from imperial medicine; 4) interest focused on colonies as productive forces or as sources of political instability; 5) the main concern went from general sanitary measurements to the search for specific disease agents and their control measurements; and 6) tropical medicine becomes a postgraduate specialty. North-American imperialism shares the main characteristics of European imperialism, but the difference was centered in the sanitary measurements because Americans feared the introduction of prevalent diseases from the tropics to their territory either through Mexico or through the ports in the Atlantic or the Pacific oceans. In order to avoid this, Americans designed and implemented rigorous inspection and control measurements in the countries where they had commercial interests and in the ports where passengers and merchandise were headed to the United States. The appearance of state medicine in Latin American is a logical consequence of the implementation of the capitalistic mode of production, provided social and economic relationships between the people and the State were hardly affected and transformed by the incipient industrialization and consolidation of such a production model. This implied the consolidation of a bureaucratic mass and an increased intervention in everyday lives of the citizens via the social policies. In Colombia, the beginning of hygiene practices and, later on, of bacteriology developed in very distinctive ways. This can be observed along the x i x century, a period in which the bourgeoisie responded mainly to episodic events such as smallpox, cholera or yellow fever epidemics, which affected the whole country with different degrees of severity from both Atlantic and Pacific coasts towards the inner part of the country, threatening to reduce the population of workers and affecting the incipient commercial exchange of the country.